NEUROSYPHILIS IN THERAPEUTIC PRACTICE: CLINICAL OBSERVATION - N. A. Shostak; D. P. Kotova; A. A. Klimenko; N. G. Pravdyuk; A. V. Novikova; Yu. O. Kasha (Klinicist)
Objective: to describe a clinical case of neurosyphilis diagnosed in a therapeutic inpatient facility.Materials and methods. Female patient T., 61, was hospitalized in the therapeutic department of a general hospital with referral diagnosis of “Stage II hypertensive heart disease, risk 4. Hypertensive crisis of 03.12.2015” with complaints of general fatigue, episodes of transient memory loss with full recovery, unstable blood pressure level. The patient was examined: She underwent treponemal and nontreponemal serological tests for antibodies against Treponema рallidum, hepatitis, human immunodeficiency virus; electrocardiogram; angiography of carotid and vertebral arteries; magnetic resonance imaging (MRI)  of the brain with contrast; serological and microscopic examinations of the cerebrospinal fluid (CSF).Results. The patient»s medical history described episodes of transient global amnesia with full memory recovery, more frequent in the last year; arterial hypertension; chronic urinary tract infection; and chronic cholecystitis with frequent courses of antibacterial therapy (ceftriaxone). Since 1986, a positive serological reaction for syphilis was observed (Wassermann reaction (WR) +++) due to a history of primary syphilis. Considering reliable history of syphilis, positive serum confirmation tests for syphilis (nontreponemal: rapid plasma reagin test 3+; treponemal: passive hemagglutination reaction 4+, antibodies against T. pallidum (total) – present), history of neuropsychological symptoms (transient amnesia) and acute neurological symptoms before hospitalization (transient ischemic attack), brain MRI data (2 lesions of cerebral circulation disorders of ischemic type in the cortical branches of left and right mesencephalic arteries), a diagnosis of neurosyphilis was proposed, and lumbar puncture was performed for confirmation. Inflammatory characteristics of the CSF (cytosis 19/3, neutrophilia up to 12 cells, insignificant lymphocytosis up to 7 cells) and positive confirmation serological reactions (nontreponemal test: serum microprecipitation reaction negative, treponemal test: immunoassay: total antibodies – positivity coefficient (PC) 4.3; immunoglobulin  G – PC 2.8) were indications for standard therapy for the “neurosyphilis” diagnosis with subsequent serological control of the CSF and serum.Conclusion. The clinical case demonstrates complexity of neurosyphilis diagnosis due to a lack of pronounced clinical manifestations of the disease and advisability of a multidisciplinary approach to treatment of these patients.